(untitled) (MASKAY, 2025)
In this study, the performance of IEEE 802.11g and IEEE 802.11n wireless networks was investigated under different interference scenarios. Quality of service metrics include throughput, delay, delay variability, and packet loss rate. Experiments conducted in intra-apartment environments began with co-channel interference, with all devices connected on the same channel. Each device then broadcasts on a different channel, thereby minimizing interference. Intrusive traffic in the protocol was used for precise metrics measurements. Results indicate that performance varies depending on the standard and channel configuration. Overall, IEEE 802.11n offers superior performance, although it is more susceptible to interference compared to IEEE 802.11g. Transmission efficiency suffers significantly in the presence of co-channel interference, with throughput losses reaching up to 35% in specific scenarios. This study underscores the importance of proper channel planning to maximize throughput and mitigate the adverse effects of interference.